Effect of intense physical exercise on hepcidin levels and selected parameters of iron metabolism in rowing athletes - Skarpanska-Stejnborn, A.; Basta, P.; Trzeciak, J.; Szczesniak-Pilaczynska, L. (European Journal of Applied Physiology, 2015)
Purpose: Physical exercise, especially intense physical exercise, causes a number of unfavorable changes, including an increase in the level of pro-inflammatory cytokines with the resultant sequestration of iron in macrophages and decreased iron absorption. This can lead to a reduced supply of iron for erythroid progenitor cells and promote the development of anemia.